Tiger habitat use dynamics in Bardia-Banke Complex, Nepal using camera trap-based multi-season occupancy framework - Shah, Shyam Kumar; Karki, Jhamak Bahadur; Bhatta, Balram; Subedi, Naresh; K.C., Rabin Bahadur; Thapa, Kanchan (Nepalese Journal of Zoology, 2025)
Understanding fine-scale habitat use dynamics within species home range is crucial for long term conservation planning. We used multi-season occupancy models incorporating field and landscape level covariates to tiger camera trap data collected during the systematic periodic survey from 2013 to 2022. Habitat use probabilities varied across primary sessions, peaking at 0.56 in 2013 and dropping to 0.49 in 2022, indicating negative and positive rate of change in tiger habitat use probabilities (average lambda λ2013-2018 = 0.60, - 40% decline; average lambda λ2018-2022 = 2.28, +128% increase) between survey period 2013–2018 and 2218–2022 respectively. Local colonization probabilities fluctuated between 0.39 (SE = 0.09) during 2013–2018 and 0.48 (SE = 0.04) during 2018–2022, while local extinction remained stable at 0.50 (SE = 0.005), suggesting high site turnover. The effects of covariates on tiger habitat use dynamics varied over time. Tiger habitat use probabilities increased with proximity to waterholes and distance from settlements and decreased with elevation. However, the influence of habitat productivity and prey availability on tiger habitat use was contrary to our expectations. Colonization probability increased with prey availability and proximity to waterholes. Habitat productivity positively influenced local extinction, contrary to a priori expectations. Our findings highlight the critical role of waterhole distribution in shaping tiger habitat use in water-limited landscape. Enhancing water and prey availability can support colonization, promoting long-term persistence of tigers. Tiger habitat use dynamics highlight the importance of targeted, site-specific conservation strategies aimed at enhancing habitat suitability and promoting landscape connectivity. We emphasize the importance of long-term, multi-year camera trap monitoring to track persistence of tigers across the Complex. The study’s combination of estimated tiger habitat use and grid-based approaches offers a valuable framework for implementing targeted conservation interventions.